2018
DOI: 10.1002/ajpa.23687
|View full text |Cite
|
Sign up to set email alerts
|

Endochondral growth disruption during vitamin D deficiency rickets in a mid‐19th century series from Bethnal Green, London, UK

Abstract: Pronounced growth faltering existed in children with active rickets and affected the upper and lower limb, indicating systemic growth failures during the deficiency. Poor maternal health, early weaning and inadequate infant feeding, and lack of sunlight exposure likely contributed to the development of rickets. Complex interactions between pathological conditions, nutritional deficiencies and vitamin D deficiency may have exacerbated growth impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 92 publications
(151 reference statements)
0
6
0
1
Order By: Relevance
“…In this study, the skeletal manifestations of rickets were assessed based on the pattern of changes occurring throughout the skeleton following published criteria (Brickley et al, 2020; Ives & Humphrey, 2018; Mays et al, 2006; Ortner & Mays, 1998) but it is important to acknowledge that clinically deficient levels of vitamin D can exist without the development of the skeletal changes of the disease (e.g., Creo et al, 2017; Pettifor, 2012). This can potentially complicate paleopathological interpretations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the skeletal manifestations of rickets were assessed based on the pattern of changes occurring throughout the skeleton following published criteria (Brickley et al, 2020; Ives & Humphrey, 2018; Mays et al, 2006; Ortner & Mays, 1998) but it is important to acknowledge that clinically deficient levels of vitamin D can exist without the development of the skeletal changes of the disease (e.g., Creo et al, 2017; Pettifor, 2012). This can potentially complicate paleopathological interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…Children from post‐medieval London, UK were particularly susceptible to the development of rickets due to limited sunlight exposure related to increased pollution and rapid urbanization, and inadequate dietary intake (Ives, 2018; Ives & Humphrey, 2018; Newman & Gowland, 2017). Previous research has demonstrated pronounced growth faltering in both upper and lower limb bones in children with active changes of skeletal rickets from 19th century London (Ives & Humphrey, 2018) but less is known about the impact on cortical bone area and distribution associated with appositional growth during a period of vitamin D deficiency. This study aims to examine the impact of vitamin D deficiency rickets on the cross‐sectional area and porosity of cortical bone at the femoral midsection in a sample of children from post‐medieval London.…”
Section: Introductionmentioning
confidence: 99%
“…As such, femora from children exhibiting moderate and severe skeletal manifestations of rickets were excluded from this study. The criteria for assessing skeletal rickets for the Bethnal Green sample are detailed in previous papers (Ives, 2018; Ives & Humphrey, 2018). The children from the Christ Church Spitalfields sample were recorded using the same criteria by one of the authors (RI).…”
Section: Methodsmentioning
confidence: 99%
“…Although bioarchaeological goals of reconstructing past lifeways likely contribute to this emphasis, a greater emphasis on the physiologically integrated pathways can improve our understanding of skeletal responses to cultural factors (Agarwal, 2016; Geber & Murphy, 2012; Klaus & Tam, 2009; Watts, 2015). Studies centered on the physiological integration of the skeletal system tend to focus predominately on interactions between metabolic and skeletal systems (Brickley, 2018; Devlin, 2015; Ives & Humphrey, 2018; Snoddy et al, 2018), especially in relation to Vitamin D and C homeostasis. New research, however, is engaging with hormonal‐skeletal interactions (Gosman, Stout, & Larsen, 2011; Western & Bekvalac, 2017), and following calls for more interdisciplinary engagement (Klaus, 2014), bioarchaeologists have made strides to bridge osteoimmunology with bioarchaeology (Crespo, Klaes, Switala, & DeWitte, 2017; Rivera & Mirazón Lahr, 2017).…”
Section: Publishing Trends In Biological Anthropologymentioning
confidence: 99%